1964
DOI: 10.1139/m64-107
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro Effect of Lysostaphin on Clinical Isolates of Staphylococcus Aureus

Abstract: Lysostaphin, an antibiotic that is unique inasmuch as it lyses all strains of Staphylococcus aureus, has been tested against 252 strains obtained from clinical sources. The clinical isolates were phage typed and tested for in vitro susceptibility to lysostaphin and seven other antistaphylococcal antibiotics.The resistant strains, found generally in phage groups I, III, and Insensitive, were most susceptible to vancomycin, lysostaphin, ristocetin, and kanamycin. The antibiotics least effective were penicillin G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1965
1965
2007
2007

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…21 This enzymatic cleavage leads to destabilization of the staphylococcal cell wall, loss of osmotic equilibrium and rapid lysis of the staphylococci, often within seconds. 22 Lysostaphin is highly effective against both rapidly dividing S. aureus as well as quiescent cells, 4 and recently we have demonstrated that lysostaphin will also lyse staphylococci in biofilms killing both the sessile cells as well as disrupting the extracellular biofilm matrix. 19 A few early studies examined the potential of nonrecombinant lysostaphin, purified from S. simulans, as a therapy for S. aureus infection in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…21 This enzymatic cleavage leads to destabilization of the staphylococcal cell wall, loss of osmotic equilibrium and rapid lysis of the staphylococci, often within seconds. 22 Lysostaphin is highly effective against both rapidly dividing S. aureus as well as quiescent cells, 4 and recently we have demonstrated that lysostaphin will also lyse staphylococci in biofilms killing both the sessile cells as well as disrupting the extracellular biofilm matrix. 19 A few early studies examined the potential of nonrecombinant lysostaphin, purified from S. simulans, as a therapy for S. aureus infection in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports on the discovery and antistaphylococcal specificity of lysostaphin (Schindler and ), on its purification (Shindler and Schuhardt, 1965), on its utility against a large number of clinical strains of Staphylococcus aureus both in vitro (Schindler and Schuhardt, 1964;Cropp and Harrison, 1964;Harrison and Cropp, 1965) and in vivo (Schuhardt and Schindler, 1964), and on its enzymatic mode of action (Browder et al, Biochem. Biophys.…”
mentioning
confidence: 99%
“…A second enzyme is an acetylmuramic acid-L-alanine amidase which appears not to be bacteriolytic, per se, but only capable of acting on previously solubilized peptidoglycan (24). The major component in lysostaphin is a glycylglycine endopeptidase which is capable of specifically lysing staphylococcal cells, especially those of S. aureus (4,11,12).…”
mentioning
confidence: 99%